Influencia de las propiedades biológicas de los suelos en la producción de cultivos en Los Ríos, Ecuador - Maridueña Burgos, Holger Matheus (2025)
Ecuador is a country known for its high biodiversity per unit area in the world, with great agrobiodiversity in which crops of great importance for the country's economy are developed. However, the physical and biological characteristics of the soil of the entire region in different types of soil that are distributed in each province and its various types of crops. Therefore, this study focused on determining the influence of the biological properties of soils on crop production in the river zone, Ecuador. For this reason, an exploratory methodology was used based on recent and relevant bibliographic queries that contribute to the search for scientific information, so that results are obtained. The analyzes carried out indicate that the soils of the province of Los Ríos have moderate to high microbial activity, with a predominance of nitrogen-fixing bacteria such as Azospirillum and Rhizobium, as well as arbuscular mycorrhizal fungi that contribute to the absorption of nutrients. Finally, it was concluded that the biological properties of the soil in the Los Ríos region present a high microbial diversity, variable levels of organic matter and significant enzymatic activity, which indicates a soil with good potential for agricultural production